2018
DOI: 10.1139/cjfr-2018-0164
|View full text |Cite
|
Sign up to set email alerts
|

Histology of resin vesicles and oleoresin terpene composition of conifer seeds

Abstract: The seed coats of several conifers contain terpene-filled resin vesicles, which may be involved in the protection of the dormant embryo and the seed storage tissue against herbivores or pathogens. We analyzed the terpenoid composition of seeds from four Abies species (Abies amabilis Douglas ex J. Forbes, Abies balsamea (L.) Mill., Abies grandis (Douglas ex D. Don) Lindl., and Abies lasiocarpa (Hook.) Nutt.), two Thuja species (Thuja plicata Donn ex D. Don and Thuja occidentalis L.), and three Tsuga species (Ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The variation within a species across its geographic range was not examined. This work complements the histological examination of these resin vesicle-containing conifer seeds recently described (Kshatriya et al 2018). The percentage of seed dry weight composed of resin vesicle constituents we measured (7-D r a f t 21%) was consistent with those found for these species by other methods (Kshatriya et al 2018), and with the 20% reported in the European silver fir (Abies alba Mill.)…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The variation within a species across its geographic range was not examined. This work complements the histological examination of these resin vesicle-containing conifer seeds recently described (Kshatriya et al 2018). The percentage of seed dry weight composed of resin vesicle constituents we measured (7-D r a f t 21%) was consistent with those found for these species by other methods (Kshatriya et al 2018), and with the 20% reported in the European silver fir (Abies alba Mill.)…”
Section: Discussionsupporting
confidence: 69%
“…Smirnoff 1972;Zavarin et al 1977). Kshatriya et al (2018) have recently identified and quantified the monoterpenes and diterpenoids found in these and the other resin vesicle-containing conifer seeds studied here. Additional studies are needed to establish whether these ketones confer this difference in inhibitory potency, and to quantify the inhibitory potency of each resin vesicle constituent.…”
Section: Significantly Higher Potency Of Thuja Versus Abies Resin Vesicle Extracts Was Observedmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, structurally related labdane-type diterpenoids, such as ferruginol and derivative compounds, act as defence metabolites in many Cupressaceae species [3,7,8]. On the other hand, diterpene resin acids (DRAs), together with mono-and sesqui-terpenes, are the main components of the oleoresin defence system in the Pinaceae species (e.g., conifers), and have been shown to provide an effective barrier against stem-boring weevils and associated pathogenic fungi [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One seed species, white pine Pinus strobus , represented a highly preferred seed for Peromyscus maniculatus and the other, balsam fir Abies balsamea , represented a seed of low preference (Abbott 1962, Duchesne et al 2000, Boone and Mortelliti 2019) (Supporting information). With a relatively low handling time, white pine delivers approximately 0.102 kcal/seed, while balsam fir has only 0.046 kcal/seed (Boone and Mortelliti 2019) and unpalatable secondary compounds (resins and terpenes) (Lobo and Millar 2011, Kshatriya et al 2018). White pine is slightly larger than balsam fir, by approximately 0.01 g (Boone and Mortelliti 2019) (Supporting information).…”
Section: Methodsmentioning
confidence: 99%